Atomic‐Scale Modulation of Synthetic Magnetic Order in Oxide Superlattices (Small Methods 2/2023). Issue 2 (17th February 2023) - Jeong, Seung Gyo; Song, Sehwan; Park, Sungkyun; Lauter, Valeria; Choi, Woo Seok
Abstract : Polarized Neutron Reflectivity In article number 2201386, Choi and co‐workers showed that polarized neutron reflectivity (PNR) provides a small probe for spin orientation in quantum materials. The spin vectors in each atomic layer can be resolved with PNR. Combined with atomic‐scale precision epitaxy and controllable spin textures, the customized synthetic magnetic order can be visualized.